2014
DOI: 10.1088/0004-637x/789/1/10
|View full text |Cite
|
Sign up to set email alerts
|

The Close Binary Frequency of Wolf-Rayet Stars as a Function of Metallicity in M31 and M33

Abstract: Massive star evolutionary models generally predict the correct ratio of WCtype and WN-type Wolf-Rayet stars at low metallicities, but underestimate the ratio at higher (solar and above) metallicities. One possible explanation for this failure is perhaps single-star models are not sufficient and Roche-lobe overflow in close binaries is necessary to produce the "extra" WC stars at higher metallicities. However, this would require the frequency of close massive binaries to be metallicity dependent. Here we test t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…More recently, in 2014, Neugent et al obtained multi-epoch spectra of nearly all of the WRs in M31 and M33 and searched for short period binary systems by observing radial velocity variations within the prominent emission and hydrogen absorption lines. Such hydrogen lines tend to suggest the presence of an O-type star companion (with the notable exceptions being the WN3/O3s, and some hydrogen-rich WRs found in the Galaxy and in the SMC) [134]. This study found that ∼30% of the WRs within M31 and M33 were in short-period binary systems.…”
Section: Binaritymentioning
confidence: 61%
“…More recently, in 2014, Neugent et al obtained multi-epoch spectra of nearly all of the WRs in M31 and M33 and searched for short period binary systems by observing radial velocity variations within the prominent emission and hydrogen absorption lines. Such hydrogen lines tend to suggest the presence of an O-type star companion (with the notable exceptions being the WN3/O3s, and some hydrogen-rich WRs found in the Galaxy and in the SMC) [134]. This study found that ∼30% of the WRs within M31 and M33 were in short-period binary systems.…”
Section: Binaritymentioning
confidence: 61%
“…We find no evidence that this separation is due to a gradient in exposure time or detector location in the observations. Instead, the separation may point to a metallicity effect, as there is a known chemical abundance gradient in M33, with the highest metallicities occurring at galaxy center and decreasing outwards (Magrini et al 2007;Neugent & Massey 2014). In particular, (Magrini et al 2007) measure this gradient as comprised of two slopes with the break occurring at R ∼ 3 kpc, similar to the radius at which we see the separation between the two histograms in Figure 14.…”
Section: Detectabilitymentioning
confidence: 67%
“…The relative importance of either channel remains however an ongoing debate (e.g. Vanbeveren et al 1998;Neugent & Massey 2014;Shenar et al 2020). In this context, establishing the evolutionary status of WRs in binary systems is of particular interest as it may offer ways to better constrain the impact of multiplicity on its evolutionary history and, from there, refine our physical understanding of binary evolution.…”
Section: Introductionmentioning
confidence: 99%